A Questionnaire Study on Euthanasia in Farm-Raised Mink - Korhonen, Hannu T; Sepponen, Juhani; Eskeli, Pekka (EDUCARE, 2013)
ABSTRACT: A questionnaire was formulated to collect data on euthanasia procedures and routines in farmed mink. The principle aim was to clarify the extent and functionality of the main killing methods, i.e. filtered exhaust and cylinder CO (carbon monoxide) and cylinder CO2 (carbon dioxide). The questionnaire was sent to 397 mink farms in Finland and to 143 in the Netherlands. The final response rates were 34.3% for Finland and 24.5% for the Netherlands. The farms in the Netherlands were typically larger than those in Finland. The preferred method of euthanasia in the Netherlands is cylinder CO, which has been shown to work well in that countrys farming system. In Finland, the filtered exhaust CO killing method has a long history, and farmers have grown accustomed to using this special method. The results were as follows: 20.0% of farmers listened outside the killing box, and when there was no sound, they presumed the animals were dead; 20.0% of farmers checked the state of the animals through the inspection window of the box before opening it; 80.0% of farmers waited for 5 minutes or more after the last mink was put into the box before emptying it; 45.7% farmers inspected each individual mink when emptying the box, checking for breathing and movement; and 14.3%Â  of farmers inspected the mink at the cooling site, checking for breathing and movement. The replies to our questionnaire study suggest that farmers consider that all three euthanasia methods, cylinder CO, cylinder CO2 and filtered exhaust CO are effective and useful ways of killing mink in farming practice.KEY WORDS: Mustela vison, killing methods, social welfare, gas euthanasia, fur farming, and Finland and Netherlandsâ farmers.Â About the Authors: Hannu T. Korhonen, Juhani Sepponen and Pekka Eskeli are Principal Research Scientists and Ph.D. Docents in Applied Zoology, Animal Production Research, MTT (Agrifood Research Finland) SilmÃ¤jÃ¤rventie 2, 69100 Kannus, Finland. The authors can be contacted via e-mail at: hannu.t.korhonen@mtt.fiHow to cite this article? Korhonen, Hannu T., Juhani Sepponen & Pekka Eskeli. (2013). âA Questionnaire Study on Euthanasia in Farm-Raised Minkâ in EDUCARE: International Journal for Educational Studies, Vol.5(2) February, pp.241-250. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 20, 2012); Revised (January 25, 2013); and Published (February 17, 2013).Â Â